Role Stressors and Job Performance: An Empirical Investigation in Malaysia - Nasurdin, Aizzat Mohd.; Khuan, Soon Lay (UI Scholars Hub, 2008)
The purpose of this study was to empirically evaluate the influence of role stressors (role conflict and role ambiguity) in predicting job performace (task performance and contextual performance). Survey data was drawn from a sample of 136 customer-contact employees within the telecomunications industry of Malaysia. Results of the regression analyses showed that role conflict alone had a significant and negative relationship with task performance. On the other hand, both role conflict and role ambiguity were found to be significantly and negatively related to contextual performance. Implications of the findings and directions for future research are discussed.